Inheritance and Quantitative Trait Locus Mapping of Fusarium Wilt Resistance in Cucumber - Dong, Jingping; Xu, Jun; Xu, Xuewen; Xu, Qiang; Chen, Xuehao (Frontiers in Plant Science, 2019)
Fusarium wilt (FW) is a very serious soil-borne disease worldwide, which usually results in huge yield losses in cucumber production. However, the inheritance and molecular mechanism of the response to FW are still unknown in cucumber (Cucumis sativus L.). In this study, two inbred cucumber lines Superina (P1) and Rijiecheng (P2) were used as the sensitive and resistant lines, respectively. A mixed major gene plus polygene inheritance model was used to analyze the resistance to FW in different generations of cucumber, namely, P1, P2, F1 (P1×P2), B1, and B2, obtained by backcrossing F1 plants with Superina (B1) or Rijiecheng (B2), and F2, obtained by self-crossing the F1 plants. After screening 18 genetic models, we chose the E-1 model, which included two pairs of additive-dominance-epistatic major genes and additive-dominance polygenes, as the optimal model for resistance to FW on the basis of fitness tests. The major effect quantitative trait locus (QTL) fw2.1 was detected in a 1.91-Mb-long region of chromosome 2 by bulked-segregant analysis. We used five insertion/deletion markers to fine-map the fw2.1 to a 0.60 Mb interval from 1,248,093 to 1,817,308 bp on chromosome 2 that contained 80 candidate genes. We also used the transcriptome data of Rijiecheng inoculated with Fusarium oxysporum f. sp. cucumerinum (Foc) to screen the candidate genes. Twelve differentially expressed genes were detected in fw2.1, and five of them were significantly induced by FW. The expression levels of the five genes were higher in FW-resistant Rijiecheng inoculated with Foc than in the control inoculated with water. Our results will contribute to a better understanding of the genetic basis of FW resistance in cucumber, which may help in breeding FW-resistant cucumber lines in the future.